Tapered optical fibre sensors: current trends and future perspectives - Korposh, Sergiy; James, Stephen W.; Lee, Seung-Woo; Tatam, Ralph P. (MDPI, 2019)
The development of reliable, affordable and efficient sensors is a key step in providing tools for efficient monitoring of critical environmental parameters. This review focuses on the use of tapered optical fibres as an environmental sensing platform. Tapered fibres allow access to the evanescent wave of the propagating mode, which can be exploited to facilitate chemical sensing by spectroscopic evaluation of the medium surrounding the optical fibre, by measurement of the refractive index of the medium, or by coupling to other waveguides formed of chemically sensitive materials. In addition, the reduced diameter of the tapered section of the optical fibre can offer benefits when measuring physical parameters such as strain and temperature. A review of the basic sensing platforms implemented using tapered optical fibres and their application for development of fibre-optic physical, chemical and bio-sensors is presented.
Keywords: whispering gallery mode; functional nano-thin coatings; evanescent wave spectroscopy; tapered optical fibre sensors; modal interferometry